In Search of the Culprit Aspects of Medieval Authorship - Rösli, Lukas; Gropper, Stefanie (Andere Ästhetik - Studien, 2021)
Despite poststructuralist rejections of the idea of a singular author-genius, the question of a textual archetype that can be assigned to a named author is still a common scholarly phantasm. This volume sets new standards by applying current theoretical approaches to the question of concepts of authorship in medieval and early modern literature. The basic thesis is that authorship is a narratological function rather than an extra-textual entity.